The ErbB1-dependent effect of recombinant epidermal growth factor (rEGF) against lapatinib-induced cytotoxicity in Caco-2 human intestinal cells / Raja Nur Firzanah Syaza Raja Sharin ... [et al.] - Raja Sharin, Raja Nur Firzanah Syaza; Wan Mohamad Zain, Wan Nor I’zzah; Khan, Jesmine; Ibahim, Mohammad Johari (Universiti Teknologi MARA, Pulau Pinang, 2022)
Lapatinib, an orally administered dual ErbB1 and ErbB2 tyrosine kinase inhibitor, is an FDA-approved treatment for ErbB2-positive breast tumour. However, diarrhoea is one of the major drawbacks for this treatment. Incidence of lapatinib-induced diarrhoea (LID) has been reported as high as 58-78% of treated patients, with 23.3-25% grade 3-4 cases. Although diarrhoea seems tolerable, prolonged diarrhoea can cause malnutrition, hospitalization and interfere with cancer treatment. Thus, diarrhoea can compromise the quality of life of patients with cancer. ErbB1 is widely expressed in the intestine which functions to maintain homeostasis. Thus, ErbB1 is hypothesised to be involved in LID mechanism through its inhibition by lapatinib in the intestine. The investigation aims to determine the cytotoxicity effect of lapatinib on Caco-2, a human colon adenocarcinoma cell line, and to determine whether recombinant epidermal growth factor (rEGF) could counteract lapatinib action. The experiments were conducted using water-soluble tetrazolium salt (WST-1) cell viability assay. Caco-2 was selected as an in vitro model as it is able to differentiate into enterocytes-like phenotype, hence reflecting small intestinal epithelium. Caco-2 was treated with a range of concentrations of lapatinib (0-100μM) and incubated at 24, 48, 72 and 96 hours. Lapatinib showed different inhibitory concentrations (IC50) at different time-points, with no IC50 observed at 24 hours. Recorded IC50 values are 28μM ±12.81, 29μM ±2.51 and 14μM ±1.64 at 48, 72 and 96 hours, respectively. The median half maximal IC50 of lapatinib; 28.00μM ±2.51 over 48-96 hours was treated on Caco-2 in combination with rEGF (150-1000nM). rEGF was able to promote 35.5% cell proliferation in lapatinib-treated cells at 325nM±5.18. Overall, rEGF counteracts lapatinib-induced cytotoxicity on the intestinal cells which proves lapatinib interaction with ErbB1 that leads to LID. However further investigations are required